2006
DOI: 10.1016/j.jcrs.2006.02.064
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous bilateral cataract surgery: Financial differences among nations and jurisdictions

Abstract: Results show that discounting second-eye cataract surgery in simultaneous bilateral cataract surgery was a financial deterrent. Although increased efficiency was a slight incentive to ophthalmologists and surgical centers, anesthesiologists experienced significant financial disincentives.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
42
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(44 citation statements)
references
References 13 publications
1
42
0
1
Order By: Relevance
“…5 A growing number of peer-reviewed publications support the increasing use of ISBCS worldwide. [3][4][5][6][7][8][9][10][11] Arguments in favor of ISBCS are based on assumptions about the efficiency of this procedure and faster improvements in patient autonomy and health-related quality of life (HRQL). 2 However, the main justification for DSBCS is the risk for serious bilateral complications, such as endophthalmitis and suboptimum refractive outcomes, that is associated with ISBCS.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…5 A growing number of peer-reviewed publications support the increasing use of ISBCS worldwide. [3][4][5][6][7][8][9][10][11] Arguments in favor of ISBCS are based on assumptions about the efficiency of this procedure and faster improvements in patient autonomy and health-related quality of life (HRQL). 2 However, the main justification for DSBCS is the risk for serious bilateral complications, such as endophthalmitis and suboptimum refractive outcomes, that is associated with ISBCS.…”
mentioning
confidence: 99%
“…One recent clinical trial 15 and 1 economic analysis 16 support the previous findings in several case series. [3][4][5][6][7][8][9][10][11] These studies found that patients treated with ISBCS recovered visual function faster with no increase in the risk for relevant complications. Very few prospective comparative randomized studies have examined the safety and effectiveness of ISBCS versus DSBCS.…”
mentioning
confidence: 99%
“…Reimbursement for same-day second eye surgery varies greatly, from 50% by Medicare and Medicaid in the United States, to no reimbursement in Japan and Israel [6]. Pressure from health insurers to reduce cost is increasing, in Switzerland ISBCE has been reimbursed by health insurers since 2009.…”
Section: Discussionmentioning
confidence: 99%
“…This is not only more convenient for the patient, but also more cost-effective and eases the demand on support infrastructure for mobilityrestricted patients [5] [6]. With an aging population these considerations will be of increased importance, particularly in an era where health care is obliged to focus on cost efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…1 Same-surgical setting second-eye cataract surgery reimbursements vary greatly from country to country: ranging from 50% to 85% of the first-eye fee for different Canadian provinces, 50% of the first-eye fee for Medicare, and 80% of the first-eye fee in the United Kingdom. 2 To my knowledge, no studies have evaluated the effect of transitioning from DSCS to ISCS on physician practices. This article will use the same cost-minimization analysis model that was used for the payer and patient perspectives but will try to fill in this gap by performing a US-based analysis from the physician perspective.…”
mentioning
confidence: 99%